Wall thinning and creep damage analysis in boiler tube and optimization of operating conditions - Begum, Shahida; Karim, A.N. Mustafizul; Zamani, A. S. M.; Shafii, M. A. (American Scientific Publishers, 2013)
The boiler tubes are operated continuously at high temperature and pressure. During operation,scales are formed in boiler tube due to tube geometries, flue gas and steam temperature. The remaining wall thickness decreases due to the formation of scale which eventually causes failure of the boiler tubes. In this investigation an iterative technique was used to determine the temperature distribution across the tube with the operating time. The operating time was considered up to 160,000 hours. The remaining life of the steam generator tube was found by finding hoop stress and Larson Miller Parameter from the Larson Miller Parameter curve for SA213-T22 material. By utilizing finite element modelling software, ANSYS 9/ANSYS 11 the temperature distribution across the steam generator tube was evaluated. The increase of heat transfer rate across the wall caused the oxide scale thickness to grow more rapidly than normal condition. It was also observed that due to formation of scale the thermal conductivity in the boiler tubes was affected and the remaining life of boiler tubes was decreased and accelerated creep damage. The ANSYS result was analyzed by Minitab 16 to determine the main and interactive effects of operating conditions. Steam temperature was influencing most the wall thinning and creep damage in comparison to the flue gas temperature. The interactive effects of both the parameters were also prominent. Moreover, the optimum operating condition was identified in order to maximizing the remnant life of the tubes while minimizing the creep rupture damage.